Clinical characterization of patients with interstitial lung disease: Report from a single Canadian Center. Issue 5 (3rd September 2021) - Fell, Charlene D.; Goobie, Gillian C.; Ford-Sahibzada, Chelsea A.; Johannson, Kerri A.
Abstract: RATIONALE: Interstitial lung diseases (ILD) are a heterogeneous group of disorders characterized by inflammation and/or fibrosis of the lung. There have been few prior descriptions of the clinical characteristics of Canadian patients with ILD. OBJECTIVES: This study aimed to characterize patients with ILD seen at a single subspecialty center in Canada. METHODS: This is a single center prospective registry of adults with ILD in Canada. Descriptive statistics were used to characterize the cohort. Linear mixed models were used to describe longitudinal changes in lung function, and Kaplan-Meier curves used to compare survival between diagnostic groups. MEASUREMENTS AND MAIN RESULTS: Baseline patient demographics, lung function studies and diagnosis as determined by a multidisciplinary team discussion were recorded. Follow-up lung function studies were collected as part of routine clinical care for patients followed in the registry. A total of 159 patients were enrolled between 2007 and 2013. The most common diagnosis was idiopathic pulmonary fibrosis (IPF) (42%), while 25% of patients had unclassifiable ILD and 22% had ILD due to connective tissue disease. Sixty-five (41%) of patients died during the mean follow-up period of 4.7 years, with IPF patients having the highest mortality. CONCLUSIONS: Patients with a wide variety of ILDs were followed at this single center subspecialty clinic, with IPF being the most frequent diagnosis. A total of 25% of patients had ILD, which was unclassifiable; most of these patients were clinically managed as IPF. Clinical outcomes of IPF patients followed in this clinic appear similar to other reported cohorts of IPF patients.